The Main Morbid Gynaecological Conditions and Client Satisfaction towards the Provided Services in Ganayen District, Suez Governorate - Attia, Mona A. S.; Hassan, Hend A.; El Rafie, Mervat M. (International Journal of Innovative Research in Medical Science, 2019)
Addressing women reproductive health (RH) problems is an important topic on the global social agenda. Thus, the current study was conducted in 2017 to study the common morbid gynaecological conditions among Ganayen primary health care (PHC) centre and mobile clinic clients in Ganayen District, Suez Governorate, Egypt and assess client satisfaction towards the provided services. A sample of 300 females aged 15-49 years complaining of the common morbid conditions, which were identified by reviewing the two PHC facilities’ records in the year 2016, and seeking medical advice from the studied PHC facilities were interviewed after receiving the service using a structured interview questionnaire and client satisfaction questionnaire, where the first 8 women who came to the centre or the clinic in the two days of work allocated for each facility were interviewed. Vaginal infection was the most common cause of seeking medical advice from the PHC centre while taking contraceptive method was the most common cause of seeking medical advice from the mobile clinic respectively. Both vaginal infection and uterine bleeding were common among hormonal contraception users. Follow-up appointments were given for only about half of women with recurrent vaginal infection. The clients were satisfied with the provided services with higher client satisfaction score for the PHC centre than the mobile clinic. Large-scale study should be conducted to explore the real situation prevailing in Egypt with objective assessment of the health facilities and health providers’ performance. Also, training of health care providers on national management protocol of common morbid condition in addition to providing health education to raise the clients’ awareness regarding these diseases are needed for proper management and prevention of recurrent and repeated attacks.